Penerapan strategi diversifikasi produk dan digital marketing pada UMKM GEMI 0418 - Erpurini, Wala; Abdurahman, Khaerul Rizal (TRIDARMA: Pengabdian Kepada Masyarakat (PkM), 2025)
Community Service Learning (KKN) is a student service program that is part of the higher education curriculum in Indonesia, in accordance with the Republic of Indonesia Law Number 20 of 2003. This program aims to connect academic theory with practice in the community, allowing students to apply the knowledge they have learned to directly help society. One of the main focuses of KKN is on Micro, Small, and Medium Enterprises (MSMEs), which play a crucial role in the economy by providing employment, income distribution, and economic growth. The method used is collaborative between students and MSMEs. The results of this KKN program include an increased use of digital marketing through Instagram social media, higher sales, product innovation, and improved confidence and independence of the MSMEs. The contributions of this KKN program are Local Economic Empowerment, Improved Human Resource (HR) Capacity, Strengthening the Relationship between Higher Education and the Community, and the Application of Academic Theory in Practice. KKN aims to enhance the digital capabilities of MSMEs, address marketing challenges, and support local economic growth through the integration of academic theory with field practice.